2013
DOI: 10.1063/1.4826579
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic distribution of extended defects and blockage of threading dislocations by stacking faults in semipolar (11¯01) GaN revealed from spatially resolved luminescence

Abstract: Spatial distribution of extended defects in semipolar (11¯01)-oriented GaN layers grown on patterned (001) Si substrates with striped grooves of varying width was investigated by optical means only using near-field scanning optical microscopy (NSOM) and cathodoluminescence (CL). A high density of basal and prismatic stacking faults was observed in the c− wings, and the threading dislocations in c+ wings, which appear as dark patterns in the NSOM and CL images, were found to bend toward the surface during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It has been demonstrated that the formation of stacking faults is connected to the epitaxial lateral overgrowth of GaN. 31,40) Different from that in the non-PSS case, during growth, the deposition of GaN occurs not only at the bottom (c-plane area), but also on top of the hemispheres, although not significantly. We suppose that the stacking order of GaN on top of the hemispheres is ABABABAB.…”
Section: Resultsmentioning
confidence: 98%
“…It has been demonstrated that the formation of stacking faults is connected to the epitaxial lateral overgrowth of GaN. 31,40) Different from that in the non-PSS case, during growth, the deposition of GaN occurs not only at the bottom (c-plane area), but also on top of the hemispheres, although not significantly. We suppose that the stacking order of GaN on top of the hemispheres is ABABABAB.…”
Section: Resultsmentioning
confidence: 98%
“…Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies have now shown that defects are also present inside semiconductor nanostructures. Thus, extended defects such as dislocations and stacking faults are observable and correlated to structural features using spatial imaging and cathodoluminescence spectroscopy (CLS) on a nanoscale [27,28,29,30,31]. Electron microscope studies have described how ZnO properties vary within interfaces, micro- and nano- structures and the effect of growth and processing methods [32,33].…”
Section: Defect Distributions In Znomentioning
confidence: 99%